Literatur Review: "Teori Manajemen Konflik Dalam Konteks Beragam: Studi Multi-Kasus Tentang Strategi, Gaya Komunikasi, Dan Dampaknya Pada Kinerja Dan Pendidikan” - Murnie Ma’ruuffah; Febi Catur Wulandari; Kholifah Miftahul Jannah; Mu’alimin Mu’alimin (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Conflict management is an essential aspect of organizational life that significantly impacts performance and productivity. This article presents research findings from four journals that discuss conflict management in various contexts. The research findings include strategies for avoiding conflict in unmarried couples facing unplanned pregnancies, communication styles of female village heads in local governance, the influence of conflict management on the performance of community health center employees, and conflict management in educational settings. These research results emphasize the importance of understanding conflict management theories, such as avoidance approaches, communication styles, and the role of communication in conflict resolution. A solid understanding of this literature provides the foundation for the development of training and educational programs in conflict management.